New Weapons to Fight against Staphylococcus aureus Skin Infections - Eliana M. Cela; Dolores Urquiza; Marisa I. Gómez; Cintia D. Gonzalez (MDPI AG, 2023)
The treatment of Staphylococcus aureus skin and soft tissue infections faces several challenges, such as the increased incidence of antibiotic-resistant strains and the fact that the antibiotics available to treat methicillin-resistant S. aureus present low bioavailability, are not easily metabolized, and cause severe secondary effects. Moreover, besides the susceptibility pattern of the S. aureus isolates detected in vitro, during patient treatment, the antibiotics may never encounter the bacteria because S. aureus hides within biofilms or inside eukaryotic cells. In addition, vascular compromise as well as other comorbidities of the patient may impede proper arrival to the skin when the antibiotic is given parenterally. In this manuscript, we revise some of the more promising strategies to improve antibiotic sensitivity, bioavailability, and delivery, including the combination of antibiotics with bactericidal nanomaterials, chemical inhibitors, antisense oligonucleotides, and lytic enzymes, among others. In addition, alternative non-antibiotic-based experimental therapies, including the delivery of antimicrobial peptides, bioactive glass nanoparticles or nanocrystalline cellulose, phototherapies, and hyperthermia, are also reviewed.